World Kidney Day; previous experience influences future directions - Samaneh Zandifar; Jyoti Baharani; Azadeh Khayyat; Mohammad Ali Esmaeil Pour; Maryam Ghasemi; Ramin Tolouian (Journal of Nephropathology)
World Kidney Day is an annual, global awareness campaign that aims to raise awareness of the importance of kidney health and hopes to alleviate the global burden of kidney diseases. It is observed annually on the second Thursday of March. The campaign focuses on elucidating various aspects of kidney health, including prevention, early detection, and management of kidney diseases. It highlights the risk factors contributing to kidney disease, such as diabetes, hypertension, dyslipidemia, metabolic syndrome, and obesity. By raising awareness about these risk factors, World Kidney Day encourages individuals to make lifestyle modifications and promptly seek medical intervention to reduce their risk factors.